Thermodynamic approach to estimating reactions and stoichiometric coefficients of anaerobic glucose and hydrogen utilization. Issue 6 (5th January 2021) - Wresta, Arini; Widyarani, Rani; Boopathy, Ramaraj; Setiadi, Tjandra
Abstract: Anaerobic digestion plays an important role in the gastrointestinal tract and in organic waste treatment. Thermodynamic analysis based on the reaction Gibbs free energy can be used to predict the favorability of some reactions occurring during anaerobic digestion. In this study, we used a thermodynamic approach to evaluating reactions and stoichiometric coefficients of the anaerobic process of in vitro rumen microbiota. The favorability of glucose, butyrate, propionate, and hydrogen utilizations was analyzed by calculating the Gibbs free energy change of each reaction. A previously published Gibbs free energy dissipation method was also used to calculate stoichiometric coefficients of the total metabolism reaction of glucose and hydrogen utilization. For glucose utilization in which the metabolism follows several different pathways, the fraction of glucose following each pathway is estimated by considering the number of electron transfer attributed throughout the catabolism reaction. Glucose utilization always occurs in the system, and the syntrophic correlation among butyrate, propionate, and hydrogen utilizations run well with propionate utilization following the alternative pathway that yields lower hydrogen. The approach applied in this research significantly reduces the stoichiometric coefficients that must be predicted in kinetic modeling. To verify the calculation result, the yield coefficients obtained were then applied in the previous mechanistic model of in vitro rumen microbiota, and the results were compared to the experimental data from literature. Abstract : Glucose utilization always occurs in the system, and the syntrophic correlation among butyrate, propionate, and hydrogen utilizations run well with propionate utilization following the alternative pathway that yields lower hydrogen. The approach applied in this research significantly reduces the stoichiometric coefficients that must be predicted in kinetic modeling. To verify the calculation result, the yield coefficients obtained were then applied in the previous mechanistic model of in vitro rumen microbiota and the results were compared to the experimental data from literature.